Preparation, structure and up-conversion luminescence properties of novel cryolite K3YF6:Er3+, Yb3+. Issue 3 (9th January 2020) - Shuai, Pengfei; Yang, Dan; Liao, Libing; Guo, Qingfeng; Mei, Lefu; Zhang, Yidi; Liu, Haikun
Abstract : Single-phase up-conversion luminescent materials K3 YF6 :Er 3+, Yb 3+ with cryolite structure were obtained for the first time. Abstract : Cryolite is a suitable host for up-conversion luminescent materials due to its low phonon energy and good optical transparency. In this work, a novel up-conversion material K3 YF6 :Yb 3+, Er 3+ with a cryolite structure was prepared successfully by a solid state method. The crystal structure, morphology, composition and up-conversion luminescence properties of the as-prepared sample were characterized by X-ray diffractometry (XRD), field emission scanning electron microscopy (SEM) and fluorescence spectrometer in detail. K3 YF6 :Er 3+, Yb 3+ has a cryolite structure. Under 980 nm excitation, the as-prepared sample can generate slight green emission at 524 and 546 nm (attributed to 2 H11/2 → 4 I15/2 transition, 4 S3/2 → 4 I15/2 transition of Er 3+ ) and strong red emission at 661 and 672 nm (corresponding to 4 F9/2 → 4 I15/2 transition, 4 I9/2 → 4 I15/2 transition of Er 3+ ). All the green and red up-conversion emission of K3 YF6 :Er 3+, Yb 3+ transfer and electronic transition process of the red and green light the sample emitted, the possible luminescence mechanism is discussed in this paper.